Phonopragmatic and Perlocutionary Effects in Islamic Motivational Rhetoric: A Case Study of Mufti Menk's Preaching - Saadiah, Nur Khofifah; Syafii, Muhammad Hisyam; Ibragimov, Sardorbek (Universitas Muhammadiyah Yogyakarta, 2025)
This study fills in the important void in phonopragmatic analyzes of Islamic motivating rhetoric in digital environments, especially how prosodic elements define doctrinal meaning and perlocutionary effects. This study seeks to understand how strategic suprasegmental phonological elements are used to produce convincing religious communications across cultural borders. Methodologically, this study uses a qualitative phonopragmatic approach, combining phonetic analysis with pragmatic interpretation. It uses PRAAT Software in Mufti Menk's lecture